Is fides quaerens intellectum a scholarly enterprise? Some thoughts on confessional theology at a public university - Gerrit Brand (Acta Theologica)
In the context of reflection in South Africa about the place of confessional theology at public universities, and in critical conversation with positions defended by thinkers like Hans Albert, Gerhard Ebeling, Ben Vedder, Vincent Brümmer and Gijsbert van den Brink, a case can be made for a legitimate place at public universities for a theology that goes beyond merely describing and analysing faith to evaluate religious points of view and suggest new ways of expressing faith drawing from a specific faith tradition, thereby serving not only the academy and broader society in general, but also specifically a faith community. Such a case can even be made within the narrow confines of a modernist understanding of what constitutes true academic scholarship, given the centrality of the notion of intersubjectivity within such an understanding.